2013
DOI: 10.1123/ijspp.8.1.57
|View full text |Cite
|
Sign up to set email alerts
|

The ACTN3 XX Genotype’s Underrepresentation in Japanese Elite Wrestlers

Abstract: Purpose:To examine the relationship between ACTN3 polymorphisms and level of athletic performance in Japanese wrestlers.Methods:The control group consisted of 243 healthy Japanese individuals. The authors divided 135 wrestlers into 3 groups based on their results in national or international competitions. They classified as elite 24 wrestlers who had placed in the top 8 in a world championship or participated in Olympic games, 28 wrestlers who had participated in world championships or become champions in Japa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
36
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
5
36
0
Order By: Relevance
“…Concerning allele frequency (Figure 2), from the studies analysed the following results were observed when combat sports athletes and controls were compared: (1) ACTN3 -no difference for the three studies that investigated it (Kikuchi et al, 2012;Kikuchi et al, 2013;Rodríguez-Romo et al, 2013); (2) ACE -two studies reported difference between the athletes and the control groups (Cieszczyk et al, 2010;Kikuchi et al, 2012); (3) PPARα -one observed higher frequency (Cieszczyk et al, 2011), but the other did not (Ahmetov et al, 2006); (4) CKM -one found a higher frequency (Fedotovskaya et al, 2013).…”
Section: Ckmmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning allele frequency (Figure 2), from the studies analysed the following results were observed when combat sports athletes and controls were compared: (1) ACTN3 -no difference for the three studies that investigated it (Kikuchi et al, 2012;Kikuchi et al, 2013;Rodríguez-Romo et al, 2013); (2) ACE -two studies reported difference between the athletes and the control groups (Cieszczyk et al, 2010;Kikuchi et al, 2012); (3) PPARα -one observed higher frequency (Cieszczyk et al, 2011), but the other did not (Ahmetov et al, 2006); (4) CKM -one found a higher frequency (Fedotovskaya et al, 2013).…”
Section: Ckmmentioning
confidence: 99%
“…To explain the differences in ACTN3 between wrestlers and controls, Kikuchi et al (2013) suggested that "individuals with the XX genotype, being completely deficient in α-actinin-3 protein, would have inferior function of skeletal muscles during the force generation of contraction or a low ability to recover from high-intensity intermittent exercise" (p.60). These factors might determine some aspects of performance in wrestling matches, which could help to explain why the ACTN3 RR allele and the RX genotype would be associated with the level of wrestlers' performance, especially in the international group analyzed by Kikuchi et al (2012).…”
Section: Ckmmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACTN3 R allele and RR genotype are associated with the upper level of the power orientation in athletes in a wide range of ethnic groups [24,26]. In a meta-analysis Alfred, et al [27] it is shown that the ACTN3 RR genotype is more common among European athletes speed and power sports than among athletes.…”
mentioning
confidence: 99%
“…These individuals are homozygous for the alleles coding a premature stop codon in the R577X (rs1815739, the transition C-to-T at nucleotide position 1729 in open reading frame ACTN3) [23,24]. Muscles pathology of these people is not observed, since α-actinin-2 compensates for its absence in muscle fibers which contraction is rapid.…”
mentioning
confidence: 99%